Timebase dynamic weight for Dijkstra Algorithm implementation in route planning software - Rosyidi, Lukman; Pradityo, Hening Pram; Gunawan, Dedi; Sari, Riri Fitri (2014 International Conference on Intelligent Green Building and Smart Grid (IGBSG), 2014)
This paper reviews Dijkstra Algorithm implementation in finding the shortest path for route planning. The regular shortest path algorithms do not consider the timebase dynamic traffic condition of road network, i.e the hourly changing of traffic density. Timebase dynamic weight for Dijkstra Algorithm compute the most efficient time and minimum fuel consumption based on the real condition of the traffic profiles of the road network. The traffic profiles describe the time needed to pass the road based on time which also differs for workdays and weekend. Simulation shows the implementation of Timebase Dynamic Weight for Dijkstra Algorithm can give better cost efficiency compared with the common Shortest Distance calculation and Traffic Avoidance calculation.